CASP4/caspase-11 promotes autophagosome formation in response to bacterial infection. Issue 11 (2nd November 2018) - Krause, Kathrin; Caution, Kyle; Badr, Asmaa; Hamilton, Kaitlin; Saleh, Abdulmuti; Patel, Khushbu; Seveau, Stephanie; Hall-Stoodley, Luanne; Hegazi, Rana; Zhang, Xiaoli; Gavrilin, Mikhail A.; Amer, Amal O.
ABSTRACT: CASP4/caspase-11-dependent inflammasome activation is important for the clearance of various Gram-negative bacteria entering the host cytosol. Additionally, CASP4 modulates the actin cytoskeleton to promote the maturation of phagosomes harboring intracellular pathogens such as Legionella pneumophila but not those enclosing nonpathogenic bacteria. Nevertheless, this non-inflammatory role of CASP4 regarding the trafficking of vacuolar bacteria remains poorly understood. Macroautophagy/autophagy, a catabolic process within eukaryotic cells, is also implicated in the elimination of intracellular pathogens such as Burkholderia cenocepacia . Here we show that CASP4-deficient macrophages exhibit a defect in autophagosome formation in response to B. cenocepacia infection. The absence of CASP4 causes an accumulation of the small GTPase RAB7, reduced colocalization of B. cenocepacia with LC3 and acidic compartments accompanied by increased bacterial replication in vitro and in vivo . Together, our data reveal a novel role of CASP4 in regulating autophagy in response to B. cenocepacia infection.